2005
DOI: 10.1007/bf02504868
|View full text |Cite
|
Sign up to set email alerts
|

IDEA: Identifying design principles in educational applets

Abstract: The Internet is increasingly being used as a medium for educational software in the form of miniature applications (e.g., applets) The Internet is increasingly becoming a vehicle to design, develop, and publish educational software in the form of miniature applications (e.g., applets) that can be used to explore specific problem contexts or concepts in a domain. The design of technology tools has the potential to dramatically influence how students interact with tools, and these interactions in turn may infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Others were based on design choices reported by the designers of the software Aplusix (Nicaud et al 2004;Nicaud et al 2006). General criteria for educational applets were found in Underwood et al (2005). Principles on authoring facilities for teachers, addressing the needs of the 'neglected learners', were addressed by Sangwin and Grove (2006) and are in line with Dick's opinion that the possibility for teachers to author content themselves could bring tool and pedagogical content together (Dick 2007).…”
Section: Methodsmentioning
confidence: 97%
“…Others were based on design choices reported by the designers of the software Aplusix (Nicaud et al 2004;Nicaud et al 2006). General criteria for educational applets were found in Underwood et al (2005). Principles on authoring facilities for teachers, addressing the needs of the 'neglected learners', were addressed by Sangwin and Grove (2006) and are in line with Dick's opinion that the possibility for teachers to author content themselves could bring tool and pedagogical content together (Dick 2007).…”
Section: Methodsmentioning
confidence: 97%
“…Some of the principles Clements has suggested that are relevant to our work include recommendations that technology should provide tools for students that allow them to test ideas and receive feedback, engage in playful mathematical exploration, and directly manipulate objects. Underwood et al (2005) agree with these suggestions and also recommend that technological tools should support multiple solution strategies and approaches, employ multiple representations, and make links between representations obvious. In working with interactive diagrams (applets) that are embedded in digital textbooks, Yerushalmy (2005) suggests different functions of such diagrams -which typically include multiple representations of a concept -to narrate, complement or elaborate text found in the digital textbooks.…”
Section: Design Of Technological Tool Featuresmentioning
confidence: 80%
“…For example, a design principle that is often suggested is that students should have access to multiple representations (e.g., Underwood et al, 2005) because these representations may enable students to focus on different aspects of a mathematical idea (DuFour-Janvier, Bednarz, & Belanger, 1987). The designers of the Fish Farm tool included the pie graph and ratio count in anticipation that students could use these representations in complimentary ways (Ainsworth, 1999) to reason about the part-whole or part-part relationships.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of Design Pattern has been introduced by Alexander and Ishikawa (1977) in architecture. Later, design patterns were adopted in other fields such as software engineering (Gamma, Helm, Johnson, & Vlissides, 1994) and more recently in the field of learning and instruction (Baggetun, Rusman, & Poggi, 2004;Cristea & Garzotto, 2004;Derntl, 2004;Dimitrova & Suthcliffe, 1999;Draaijer & Hartog, 2007;Goodyear, 2005;Mislevy et al, 2003;Underwood et al, 2005) For different subject matter disciplines, it makes sense to describe design patterns. Some of these design patterns may be recognized in more than one subject matter discipline.…”
Section: Design Patterns: a Borderline Output-classmentioning
confidence: 99%